Pelatihan Budidaya Buah Tin Dan Pemasaran Melalui Media Sosial Pada Pensiunan Pegawai Swasta Kecamatan Cimanggis - Harry Budiantoro; Any Setianingrum; Perdana Wahyu Santosa; Hestin Agus Tantri Ningsih; Kanaya Lapae (Jurnal Pemberdayaan Masyarakat, 2023)
Fig cultivation is a hobby-based economic activity that can help families in Cimanggis District, Depok City, West Java, meet their income needs. The overall goal of this activity is to teach retirees how to do it. Figs (Tin) were chosen because of their high social and economic value as well as their simplicity and low seed costs. To produce tangible benefits, such as economic benefits and standardized and high-value products, this activity is carried out through a plant cultivation training process guided by competent resource persons. This activity specifically aims to equip retirees with the necessary knowledge and skills to grow fig plants and produce figs. In addition, when this activity is practiced, the target output will be met. Among them are activity posters, activity videos posted on social media sites such as YouTube, YARSI TV, and Facebook, online articles in print media such as newspapers and magazines, as well as articles in online community service journals with an ISSN. Based on the findings of field research, the majority of the population aged over 55 years still shows high enthusiasm and activity productivity. The average value of the questionnaire before this activity was 33% and after this activity was carried out, the average value of the questionnaire results was 76%.